Untreated or ammoniated cotton gin trash in the ensiling of elephant grass reduces silage quality - Danilo Gusmão de Quadros; Alexandro Pereira Andrade; Guilherme Soares de Souza; Fagner Estevam da Silva; Edwilka Oliveira Cavalcante (Acta Scientiarum. Animal Sciences, 2022)
This study examined the inclusion of untreated or urea-ammoniated CGT on the chemical composition, pH, gas, and effluent losses, dry matter recovery (DMR), and aerobic stability of elephantgrass silage. The experiment was laid out in a randomized design with a 3 × 3 factorial arrangement represented by three levels of inclusion of CGT during ensiling (0, 5, or 10%) and three levels of ammoniation of CGT with urea before ensiling (0, 4 or 8% for 28 days), using four replications. Data were subjected to analysis of variance and Tukey's test, considering a 5% significance level. The pH and DM, NDIN, ADIN, NDF and ADF contents of the silages increased (p < 0.05) with the inclusion of CGT, regardless of ammoniation. The lowest (p < 0.05) effluent loss was achieved using 10% of CGT ammoniated with 8% urea. In contrast, the elephantgrass silage exhibited the lowest (p < 0.05) gas loss and the greatest (p < 0.05) DMR. The inclusion of CGT compromised the aerobic stability of the silage. Therefore, the inclusion of CGT – either untreated or ammoniated – in the ensiling of elephantgrass is not recommended.